The Statues of St. John of Nepomuk in Olomouc and Žarošice. The Paper Towards Recognition of the Baroque Sculpture in Moravia (Theatrum historiae, 2006)
The paper deals with a baroque visual tradition of the two themes of the St. John of Nepomuk´s iconography in the baroque sculpture of Bohemia and Moravia: martyr´s dropping from the Prague´s Charles Bridge to the river and St. John as a beadsman. It finds the inspiration of these fully narrative themes in the literary tradition of martyr´s official hagiography, in the writings of the patriotic Jesuit Bohuslav Balbinus (Vita B. Joannis Nepomuceni, 1670-1671), in baroque homiletics and in the contemporary graphic prints. There are two most effectual repeats of our topics within the Moravian Baroque sculpture production: the statue in Žarošice and the statue in Olomouc. The paper newly ascribes the piece in Žarošice, anonymous until today, to the work of Jan Jiří Schauberger and it puts its dating to the turn of 1730s and 1740s. The paper further newly interprets the unusual configuration of St. John´s statue in Olomouc standing in front of the Hradisko monastery, which was executed by Josef Antonín Winterhalder. St. John of Nepomuk is presented here as the heavenly protector of all ages of human generations which are represented by three suppliants: infant, juvenile and old man. The paper gives the new interpretation of the unique scene, which has no iconography parallel in the baroque sculpture of Bohemia and Moravia.